Caudal vena cava isolation using ablation index‐guided radiofrequency catheter ablation (CARTO™ 3) to treat sustained atrial tachycardia in horses - Eva Buschmann; Glenn Van Steenkiste; Ingrid Vernemmen; Marie Demeyere; Stijn Schauvliege; Annelies Decloedt; Gunther vanLoon (Journal of Veterinary Internal Medicine)
Abstract Background Myocardial sleeves of the caudal vena cava are the predilection site for atrial tachycardia (AT) in horses. Caudal vena cava isolation guided by the ablation index, a lesion quality marker incorporating power, duration and contact force, might improve outcome. Objectives Describe the feasibility and outcome of caudal vena cava isolation using ablation index‐guided radiofrequency catheter ablation (RFCA) to treat AT in horses. Animals Ten horses with sustained AT. Methods Records from 10 horses with sustained AT treated by three‐dimensional electro‐anatomical mapping and ablation index‐guided RFCA (CARTO™ 3) were reviewed. Results Three‐dimensional electro‐anatomical mapping of the right atrium identified a macro‐reentry circuit in the caudomedial right atrium (n = 10). Point‐by‐point RFCA was performed to isolate the myocardial sleeves of the caudal vena cava in power‐controlled mode with a mean of 17 ± 7 applications. The ablation index target was 400‐450. A median ablation index of 436 (range, 311‐763) was reached using a median maximum power of 35 (range, 24‐45) W for a median duration of 20 (range, 8‐45) seconds, with a median contact force of 10 (range, 3‐48) g. Sinus rhythm was restored in all 10 horses. To date, 9‐37 months post‐ablation, none of the horses have had recurrence. Conclusions and Clinical Importance Caudal vena cava isolation using ablation index‐guided RFCA was feasible and effective to permanently treat sustained AT in horses. Ablation index guidance ensured efficient lesion creation, and isolation of the caudal vena cava eliminated the arrhythmogenic substrate, thereby minimizing the risk of recurrence.